Magnesium Alloys for Hydrogen Storage Processed by ECAP Followed by Low Temperature Rolling - Silva, W. B.; Leiva, D. R.; Floriano, R.; Vega, L. E. R.; Oliveira, V. B.; Gallego, J. [UNESP]; Figueroa, S. J. A.; Miqueles, E. X.; Silva, E. P.; Ishikawa, T. T.; Botta, W. J. (Univ Fed Sao Carlos, Dept Engenharia Materials, 2022)
The hydrogen storage properties of pure magnesium and magnesium ZK60 alloy containing 2.5 wt% of mischmetal (Mm) processed by Cold Rolling (CR) and Low Temperature Rolling (LTR) were investigated. Before CR and LTR processing, Equal Channel Angular Pressing (ECAP) was employed in the alloys as an initial processing step to refine their microstructures. Microstructure findings showed that the ECAP+LTR route is more effective than the others to generate grain refinement - a desirable aspect in hydrogen storage materials. SEM and TEM results in combination with XPS analysis revealed that the ZK60 + 2.5 wt. % Mm alloy after being processed by ECAP + LTR had more refined grains (with sizes < 1 mu m) and exhibited superior resistance to the formation of oxides and/or hydroxides when compared with the pure magnesium alloy. The refined microstructures of the ECAP+LTR samples combined with the presence of highly oriented grains along to the (002) plane and large amount of defects - which are features associated to the LTR route - such as cracks and voids, resulted in a fast activation kinetics than for the samples processed by ECAP + CR route.
Keywords: Mg-Alloys; Low-Temperature rolling; ECAP; Hydrogen storage; Metal hydrides